2023
DOI: 10.1101/2023.02.06.527263
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pharmacological inhibition of astrocytic transglutaminase 2 facilitates the expression of a neurosupportive astrocyte reactive phenotype in association with increased histone acetylation

Abstract: AAstrocytes are the primary support cells of the central nervous system (CNS) that help maintain the energetic requirements and homeostatic environment of neurons. CNS injury causes astrocytes to take on reactive phenotypes with altered overall function that can range from supportive to harmful for recovering neurons. The characterization of reactive astrocyte populations is a rapidly developing field, and the underlying factors and signaling pathways governing which type of reactive phenotype that astrocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(18 citation statements)
references
References 92 publications
1
17
0
Order By: Relevance
“…There is growing evidence that TG2 plays a significant role in regulating the phenotype of reactive astrocytes (Espitia Pinzon et al 2017, van Strien et al 2011b, Elahi et al 2021, Emerson et al 2023, Monteagudo et al 2018, Delgado and Johnson 2024. In different injury models, it has been demonstrated that deletion or depletion of TG2 from astrocytes enhances their ability to support neuronal viability and recovery after injury compared to controls (Colak and Johnson 2012, Elahi et al 2021, Emerson et al 2023, Monteagudo et al 2018. Most notably, mice with astrocyte-specific TG2 deletion recover motor function significantly faster and to an overall greater extent after SCI compared to WT mice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…There is growing evidence that TG2 plays a significant role in regulating the phenotype of reactive astrocytes (Espitia Pinzon et al 2017, van Strien et al 2011b, Elahi et al 2021, Emerson et al 2023, Monteagudo et al 2018, Delgado and Johnson 2024. In different injury models, it has been demonstrated that deletion or depletion of TG2 from astrocytes enhances their ability to support neuronal viability and recovery after injury compared to controls (Colak and Johnson 2012, Elahi et al 2021, Emerson et al 2023, Monteagudo et al 2018. Most notably, mice with astrocyte-specific TG2 deletion recover motor function significantly faster and to an overall greater extent after SCI compared to WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear fractionation has shown that TG2 is enriched in the chromatin fraction (Lesort et al 1998). IT exhibits a functionally significant interaction with the transcription factor-like protein Zbtb7a, which regulates gene expression in part by altering promoter accessibility (Emerson et al 2023, Pittol et al 2018. To interrogate how VA4 may alter the interaction of TG2 with Zbtb7a, and thus gene expression, HEK cells were transfected with V5-tagged TG2 and FLAG-tagged Zbtb7a, followed by VA4 or vehicle-only treatment and subsequent analysis of TG2-Zbtb7a interactions (Emerson et al 2023).…”
Section: Immunoprecipitation Of Tg2 and Zbtb7a After Va4 Treatmentmentioning
confidence: 99%
See 3 more Smart Citations